Anti-inflammatory Properties of the Monoterpene 1.8-cineole: Current Evidence for Co-medication in Inflammatory Airway Diseases - Juergens, U. R. (Drug Research, 2014)
1,8-cineole is a natural monoterpene, also known as eucalyptol. It is a major compound of many plant essential oils, mainly extracted from Eucalyptus globulus oil. As an isolated compound, 1,8-cineole is known for its mucolytic and spasmolytic action on the respiratory tract, with proven clinical efficacy. 1,8-cineole has also shown therapeutic benefits in inflammatory airway diseases, such as asthma and chronic obstructive pulmonary disease (COPD). This clinical evidence refers to its anti-inflammatory and anti-oxidant mode of action, which has been proven in numerous pre-clinical studies. In vitro studies found strong evidence that 1,8-cineole controls inflammatory processes and mediator production of infection- or inflammation-induced mucus hypersecretion by its action as anti-inflammatory modifier rather than a simple mucolytic agent. The aim of this review is to present these preclinical studies performed with the pure monoterpene, and to summarize the current knowledge on the mode of action of 1,8-cineole. The actual understanding of the pure 1,8-cineole compared to mixtures of natural volatile oils containing 1,8-cineole as a major compound and to mixtures of natural terpenes, known as essential oils, will be discussed. Based on the anti-oxidative and anti-inflammatory properties, recent clinical trials with 1,8-cineole have shown first evidence for the beneficial use of 1,8-cineole as long-term therapy in the prevention of COPD-exacerbations and to improve asthma control.
Keywords: 1,8-cineole; superoxides; inflammatory mediators; airway disease; asthma; COPD